Construction and assessment of membership to a soccer barra brava. The voices of former members - Olano-Ferreyra, María del Rosario (2023)
In this paper, we describe the construction and assessment of membership to a football barra brava from the voices of a group of former members. We developed semi-structured interviews with seven former members of the barra brava Trinchera Norte (Peru), who attended the stadiums in the 1990s and played a leading role in the barra brava. The participants tell us that they built their membership from the interaction with a group of peers who shared an interest in a soccer team. In this group, behaviors that they assumed and that stand out today were developed and defined. Thus, they value camaraderie, resilience, pride and the fight for their goals and ideals as significant learning that they continue to apply in their lives. © 2023 Universitat Autonoma de Barcelona.